แนวทางการพัฒนาชุมชนแห่งการเรียนรู้ทางวิชาชีพด้านสะเต็มศึกษา ของโรงเรียนเอกชนเครือข่ายสะเต็มศึกษาสมทบ กลุ่มภาคเหนือตอนล่าง - จิตรแก้ว พงษ์ไชย (จุฬาลงกรณ์มหาวิทยาลัย, 2018)
The objectives of this research were 1) to study the present and the desirable states of developing the professional learning community in STEM Education for STEM Education private school network in the lower northern region 2) to propose approaches for developing the professional learning community in STEM Education for STEM Education private school network in the lower northern region. The population was the members of STEM Education private school network in the lower northern region. The informants were the Principal, the Assistant Principal and the teachers; 68 in total. The research instruments were rating scale questionnaires and rating scale appropriability and possibility of evaluation forms. The data were analyzed by frequency distribution, percentage, mean, standard deviation, PNI Modified and content analysis. The results were as follows: the present and the desirable states in developing the professional learning community in STEM Education for STEM Education private school network in the lower northern region were at the medium level (M=2.65) and high level (M=4.40) respectively. The first priority needs index was planning a systematic practice (PNIModified=0.699); the second priority needs index was improving practice (PNIModified=0.682); and the last priority needs index was identifying the focus by setting shared vision, mission and goal (PNIModified=0.601) There were five approaches for developing the professional learning community in STEM Education for STEM Education private school network in the lower northern region. The approaches sort by priority needs index were 1) developing the planning a systematic practice process in STEM Education curriculum design 2) developing the improving STEM Education curriculum design practice process 3) developing the sharing outcome process in budgeting management for STEM Education 4) developing the applying and reflecting process in STEM Education curriculum design 5) developing the identifying the focus by setting shared vision, mission and goal process in budgeting management for STEM Education.